Medical-surgical nursing care - Burke, Karen M. 4 0 16; Mohn-Brown, Elaine.;Eby, Linda; 5 (Upper Saddle River, New Jersey : Pearson, 2011)
Answers the question, what do practical vocational nurses need to know and to be able to do in order to deliver safe and effective medical-surgical nursing care? This comprehensive book, in a brand new 3rd edition, prepares basic practical/vocational nursing students to care for adult clients with medical or surgical disorders or diseases. Completely updated with new information and an emphasis on the nursing role, it explains the risk factors, causes, and pathophysiology of common disorders and diseases, and reviews diagnostic tests and medical management of the disorders. A focus on nursing care is presented in a nursing process format - including assessment data to collect, nursing diagnoses with suggested interventions and their rationales, and evaluation data to determine the effectiveness of nursing care. Some exciting features include: Nursing process care plans; Critical thinking self-checks; Rationale for each nursing intervention; and Nursing care and procedure checklists.--BOOK JACKET.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; methods. -- Surgical nursing.;Nursing.;Nursing Care;Nursing Process. -- 20; 20; 2